Localization of Basicranium Midline by Submentovertex Projection for the Evaluation of Condylar Asymmetry. (18th January 2012) - Maglione, Michele; Costantinides, Fulvia
Abstract : The purpose of this research was to compare the reliability of two different methods for cranial midline localization through cephalometric analysis of mandibular condyle asymmetries. A retrospective cohort study was performed analyzing consecutively the SMV radiograms of 47 patients undergoing oral surgery before orthodontic treatment at the Dental School, University of Trieste (Italy) from 2003 to 2008. Two different cephalometric analyses were used to identify the basicranium midline (Tracing 1: initial landmarks = craniostat ear rods; Tracing 2: initial landmarks = spinosum foramina), and the left/right symmetry ratio (SR) for four parameters (condylar length, condylar angle, intra-condylar hemidistance, extra-condylar hemidistance) was calculated. The main result showed that no significant statistical difference between the SRs of the intra-condylar and extra-condylar hemidistance obtained with the same tracing was found (t -test;P = NS ; C.I. 95%). Conversely, the difference between the SRs obtained with the two different tracings was statistically significant (t -test;P < 0.000 ; C.I. 95%). In conclusion, if the analysis of condylar asymmetries is performed in growing subjects, utilization of anatomic references such as the neurovascular foramina seems to guarantee a lower error compared to non-fixed references such as ear rods.